Effects of Alloying Elements and Microstructure on Stainless Steel Corrosion: A Review. Issue 5 (16th December 2021) - Sun, Jianlin; Tang, Huajie; Wang, Chenglong; Han, Zhao; Li, Shisen
Abstract : Stainless steel has attracted significant attention in industrial and engineering applications. To improve its corrosion resistance, there are two major approaches that are to optimize the elemental composition and tune the microstructure. A comprehensive review of the main findings on the corrosion of stainless steel is presented, and some controversial issues are highlighted. First, the functional roles of alloying elements are discussed, including nonmetallic (B, C, and N) and metallic (Cr, Ni, Cu, and Mo) elements. Additionally, their detrimental and positive effects, as well as the corresponding mechanisms, are highlighted. Second, the microstructure‐induced corrosion of stainless steel is discussed, including the crystallographic‐orientation‐dependent corrosion, the dual influence of grain size and grain boundary distribution, texture, and defects in the matrix. In addition, nanostructured materials are mentioned herein. Third, challenges as well as research trends in the future are proposed with perspectives for the development of novel stainless steel in research and industrial applications. Abstract : The positive and negative effects of nonmetallic and metallic alloying elements on the corrosion resistance of stainless steel are shown. Their positive effects involve promoting the passive film formation, stabilizing passive film, as well as the unique intensifying effects of B, C, N. In particular, nonmetallic elements can suppress the anodic dissolution of metal by releasing oxyanions and stabilizing the electronic structure of Fe.